Evaluation of No-Drop Policies for Domestic Violence Cases in San Diego, California, Omaha, Nebraska, Klamath Falls, Oregon, and Everett, Washington, 1996-2000 - Smith, Barbara E. ([Verlag nicht ermittelbar], 2002)
This study sought to examine the effects of no-drop policies on court outcomes, victim satisfaction with the justice system, and feelings of safety. Moreover, researchers wanted to determine whether (1) prosecution without the victim's cooperation was feasible with appropriate increases in resources, (2) implementing a no-drop policy resulted in increased convictions and fewer dismissals, (3) the number of trials would increase in jurisdictions where no-drop was adopted as a result of the prosecutor's demand for a plea in cases in which victims were uncooperative or unavailable, and (4) prosecutors would have to downgrade sentence demands to persuade defense attorneys to negotiate pleas in the new context of a no-drop policy. Statutes implemented in San Diego, California, were designed to make it easier to admit certain types of evidence and thereby to increase the prosecutor's chances of succeeding in trials without victim cooperation. To assess the impact of these statutes, researchers collected official records data on a sample of domestic violence cases in which disposition occurred between 1996 and 2000 and resulted in no trial (Part 1), and cases in which disposition occurred between 1996 and 1999, and resulted in a trial (Part 2). In Everett, Washington (Part 3), Klamath Falls, Oregon (Part 4), and Omaha, Nebraska (Part 5), researchers collected data on all domestic violence cases in which disposition occurred between 1996 and 1999 and resulted in a trial. Researchers also conducted telephone interviews in the four sites with domestic violence victims whose cases resolved under the no-drop policy (Part 6) in the four sites. Variables for Part 1 include defendant's gender, court outcome, whether the defendant was sentenced to probation, jail, or counseling, and whether the counseling was for batterer, drug, or anger management. Criminal history, other domestic violence charges, and the relationship between the victim and defendant are also included. Variables for Part 2 include length of trial and outcome, witnesses for the prosecution, defendant's statements to the police, whether there were photos of the victim's injury, the scene, or the weapon, and whether medical experts testified. Criminal history and whether the defendant underwent psychological evaluation or counseling are also included. Variables for Parts 3-5 include the gender of the victim and defendant, relationship between victim and defendant, top charges and outcomes, whether the victim had to be subpoenaed, types of witnesses, if there was medical evidence, type of weapon used, if any, whether the defendant confessed, any indications that the prosecutor talked to the victim, if the victim was in court on the disposition date, the defendant's sentence, and whether the sentence included electronic surveillance, public service, substance abuse counseling, or other general counseling. Variables for Part 6 include relationship between victim and defendant, whether the victim wanted the defendant to be arrested, whether the defendant received treatment for alcohol, drugs, or domestic violence, if the court ordered the defendant to stay away from the victim, and if the victim spoke to anyone in the court system, such as the prosecutor, detective, victim advocate, defense attorney, judge, or a probation officer. The victim's satisfaction with the police, judge, prosecutor, and the justice system, and whether the defendant had continued to threaten, damage property, or abuse the victim verbally or physically are also included. Demographic variables on the victim include race, income, and level of education.